A Longitudinal Study of Acute Diarrhoeal Diseases Among Children Under Five Years in an Urban Area of Goa - Apika K Sawant; Nitin Y Dhupdale (Wolters Kluwer Medknow Publications, 2024)
Background: Acute diarrhoeal diseases (ADD) account for a large number of preventable deaths in India, especially in children less than five years who are more at risk than adults with respect to the degree of dehydration and complications. (1) To measure the incidence of ADD among children under 5 years; (2) Determine risk factors associated among children; (3) Study treatment-seeking behaviour of their mothers. Community-based, prospective, longitudinal study conducted in an urban area of Goa. Material and Methods: 250 children enrolled in the study with their mothers by stratified random sampling technique, conducted house-to-house visits every three months and mothers were interviewed with pre-tested semi-structured questionnaire. The duration of study was one year from January to December 2018. Data entered using EpiData Entry Client®, Analysed using SPSS® software version 22. Student's t-tests and Chi-square tests were used. Results: The incidence of ADD was 0.124 episodes/child/year. Significant association was noted between ADD in children and certain socio-demographic factors like child's sex, birth order, birth weight, immunization status, malnutrition, mother's age group, mother's education, and mothers' hygiene practices. Conclusions: Efforts should be made to educate all mothers about the seeking timely treatment, awareness about home-based management and their types, awareness of ORS, zinc, importance of hygienic practices like hand washing for mother and child.